2009
DOI: 10.1186/1471-2407-9-454
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial DNA content in blood samples of patients with stage I breast cancer

Abstract: BackgroundAlterations of mitochondrial DNA (mtDNA) have been implicated in carcinogenesis. We developed an accurate multiplex quantitative real-time PCR for synchronized determination of mtDNA and nuclear DNA (nDNA). We sought to investigate whether mtDNA content in the peripheral blood of breast cancer patients is associated with clinical and pathological parameters.MethodsPeripheral blood samples were collected from 60 patients with breast cancer and 51 age-matched healthy individuals as control. DNA was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 34 publications
(42 reference statements)
5
68
1
1
Order By: Relevance
“…A lower blood mtDNA level has been described in stage I breast cancer than in advanced stages II to IV, leading to suggest that cancer cells deplete a larger amount of mtDNA in circulating cells at an early stage of cancer development. The initial decline in mtDNA content should be compensated at later stage of the cancer process to restore respiratory functions (34), which is in agreement with the increase we observed in many of the gastric cancer cases studied. This kinetic of mtDNA levels during the carcinogenic process would also be in agreement with results from cohort 2 patients showing significant lower mtDNA levels in NAG and in patients with precancerous intestinal metaplasia, compared with most patients with gastric cancer.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A lower blood mtDNA level has been described in stage I breast cancer than in advanced stages II to IV, leading to suggest that cancer cells deplete a larger amount of mtDNA in circulating cells at an early stage of cancer development. The initial decline in mtDNA content should be compensated at later stage of the cancer process to restore respiratory functions (34), which is in agreement with the increase we observed in many of the gastric cancer cases studied. This kinetic of mtDNA levels during the carcinogenic process would also be in agreement with results from cohort 2 patients showing significant lower mtDNA levels in NAG and in patients with precancerous intestinal metaplasia, compared with most patients with gastric cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Levels of circulating mtDNA were found significantly higher in patients with various type of tumors (29)(30)(31)(32)44). Peripheral mtDNA content has also been proposed as a novel molecular marker for tracing tumor progression (34). In the present study, we found more variation of circulating leukocytes mtDNA level in patients with NAG or gastric cancer than in healthy subjects.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar results were obtained by Bragoszewski and collaborators (2008) in studies on ovarian cancer risk assessment. However, the significance of these results is still a subject of some controversy, since 1) low mtDNA content was identified in tumor specimens of BC at an early TNM stage (stage I) as compared with more advanced stages, suggesting that it may be essential in the early progression of BC (Xia et al, 2009), and 2) reduced mtDNA content shows a significant correlation with BC patient's ER or PR status (Yu et al, 2007). Therefore, the relationship between mtDNA content/ polymorphisms and clinicopathological characteristics of cancers remains unclear and needs further investigation, because they may influence the outcome of BC therapy, particularly endocrine treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is used as a biomarker in a number of cancers including breast, renal and gastric cancers. 13 We recently proposed the use of community sewage sensors as rapid and inexpensive alternatives to classical analytical methods for the detection of sewage biomarkers. 7 We have previously also demonstrated that community sewage sensors are able to detect a wide range of markers (e.g., prostate specific antigen 14 and illicit drugs such as cocaine 15 ).…”
mentioning
confidence: 99%